Synthesis, Self‐Assembly, and Electrocatalysis of Polyallylamine‐Functionalized Platinum Nanocubes. Issue 7 (22nd May 2013) - Fu, Gengtao; Zhao, Ruopeng; Ding, Linfei; Tao, Lin; Lin, Jun; Chen, Yu; Tang, Yawen; Zhou, Yiming; Lu, Tianhong
<x xml:space="preserve">Abstract</x> The title composite was prepared and self‐assembled on carbon nanotubes (CNTs). Even after cleaning with UV/Ozone and electrochemical methods, the residual polyallylamine strongly influences the electronic structure of Pt. The resultant Pt‐NC/CNT nanohybrid shows superior electrochemical activity and stability towards the oxygen reduction reaction in H2SO4 solutions compared with commercial Pt/C catalyst.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>